Genome-Wide Identification and Analysis of Phospholipase C Gene Family Reveals Orthologs, Co-Expression Networks, and Expression Profiling Under Abiotic Stress in Sorghum bicolor - Hongcheng Wang; Junxing Yu; Xingyu Zhang; Qian Zeng; Tuo Zeng; Lei Gu; Bin Zhu; Feng Yu; Xuye Du (Plants)
Phospholipase C (PLC) is an essential enzyme involved in lipid signaling pathways crucial for regulating plant growth and responding to environmental stress. In sorghum, 11 PLC genes have been identified, comprising 6 PI-PLCs and 5 NPCs. Through phylogenetic and interspecies collinearity analyses, structural similarities between SbPLCs and ZmPLCs proteins have been observed, with a particularly strong collinearity between SbPLCs and OsPLCs. Promoter function analysis has shown that SbPLCs are significantly enriched under abiotic stress and hormonal stimuli, like ABA, jasmonic acid, drought, high temperature, and salt. Gene co-expression networks, constructed using a weighted gene co-expression network analysis (WGCNA), highlight distinct expression patterns of SbPLC1, SbPLC3a, and SbPLC4 in response to abiotic stress, providing further insights into the expression patterns and interactions of SbPLCs under various environmental stimuli. qRT-PCR results reveal variations in expression levels among most SbPLCs members under different stress conditions (drought, NaCl, NaHCO3), hormone treatments (ABA), and developmental stages, indicating both specific and overlapping expression patterns. This comprehensive analysis offers valuable insights into the roles of SbPLCs in sorghum, shedding light on their specific expression patterns, regulatory elements, and protein interactions across different environmental stimuli and developmental stages.